Key Changes in The Customer Journey as a Result of Digitization in Trade - Galabova, Violeta; Zlatkova, Velichka (Research Papers, 2023)
Dynamic changes in consumer behaviour and digitization in retail have largely led to the emergence and development of omnichannel commerce. This, in turn, laid the foundations for the construction of a new model of customer contact, finding expression in the so-called “360-degree user experience” and the creation of an efficient customer journey. Processes are tied to defining the right set of touchpoints and integrating them to a level that provides the all-important “seamless shopping experience” for the modern consumer. In this regard, the current report emphasizes the importance of researching the specifics of the consumer path in trade and the relevant factor impacts in the undisputed leading role of digitalization.
Keywords: Customer journey; Touchpoints; Customer experience; Digitization; Retail